2019
DOI: 10.5603/kp.a2019.0030
|View full text |Cite
|
Sign up to set email alerts
|

Persistent hyperlactataemia is related to high rates of in-hospital adverse events and poor outcome in acute heart failure

Abstract: Background: Although lactate is a well-established marker in intensive care, our understanding of its utility in acute heart failure (AHF) is modest and based on studies with a single measurement of this marker. Aim: We aimed to investigate whether persistent elevation of lactate during hospitalisation is related to a higher risk of adverse events. Methods: We conducted a prospective study to assess AHF patients hospitalised in one cardiac centre. The diagnosis of persistent hyperlactataemia was based on two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…However, those patients with elevated ET‐1 had significantly lower urine sodium excretion, which only confirms the postulate for bi‐dimensional assessment of the kidney function in AHF, through the prism of natriuresis and eGFR, as two separate processes 16 . Moreover, our data suggest an interesting signal of interaction between congestion, liver dysfunction, elevation of serum lactates, and high ET‐1, all of which are signs of poor outcome in AHF 18–22 . The data from clinical trials that tested the endothelin receptor antagonists in heart failure also revealed an indirect connection between endothelin and water/sodium handling, as patients in active treatment arms of the studies tended to accumulate fluid 23 .…”
Section: Discussionsupporting
confidence: 65%
“…However, those patients with elevated ET‐1 had significantly lower urine sodium excretion, which only confirms the postulate for bi‐dimensional assessment of the kidney function in AHF, through the prism of natriuresis and eGFR, as two separate processes 16 . Moreover, our data suggest an interesting signal of interaction between congestion, liver dysfunction, elevation of serum lactates, and high ET‐1, all of which are signs of poor outcome in AHF 18–22 . The data from clinical trials that tested the endothelin receptor antagonists in heart failure also revealed an indirect connection between endothelin and water/sodium handling, as patients in active treatment arms of the studies tended to accumulate fluid 23 .…”
Section: Discussionsupporting
confidence: 65%
“…In general, a good biomarker should add clinical information that could affect the treatment of the patient and be universally available. One such new biomarker was found in the current study by Biegus et al [12]. The authors showed that persistent hyperlactataemia in 222 acute HF (AHF) patients, defined as lactate level ≥ 2 mmol/L on admission and after 24 h, was associated with more intensive HF treatment, worsening of HF and higher one-year all-cause mortality.…”
supporting
confidence: 53%
“…Cancer and pregnancy are known prothrombotic factors, which negatively alter fibrin clot phenotype [38,39] and modulate NET formation [39,40]. Third, all laboratory parameters were assessed on admission, while hyperlactatemia may be persistent [41] and might modulate inflammatory response and coagulation activation.…”
Section: Discussionmentioning
confidence: 99%